CONSIDERATIONS ON THE PROCEDURE OF REDUCED VALUE APPLICATION IN THE REGULATION OF THE NEW CODE OF CIVIL PROCEDURE - Licuta, PETRIA (Strategii Manageriale)
The reduced value application procedure is regulated by the New Code of Civil Procedure, in art. 1025-1032, and it purposes to settle the litigations presented for judgment with expediency. The procedure is enforced in the case of applications having a maximum value of 10,000 lei at the date of court notification, and this amount does not include interests, court expenses and other accessory revenues. In the enforcement of the procedure, both the value of the application, and its object shall be taken into account, as the legislator expressly provided in art. 1025 para. (2) and (3) the situations to which this procedure does not apply. The work approaches the aspects related to the reduced value application procedure, from the point of view of the provisions of art. 1025-1032 from the Code of civil procedure in force, and the aspects referring to the area of application, the competent law court, opening and settlement of the procedure.